Temporary clamping of the uterine arteries versus coventional technique for the prevention of postpartum hemorrage during cesarean section: a randomized controlled trial study. - Gómez-Castellano, Manuel; Sabonet-Morente, Lorena; Jiménez-López-, Jesus Salvador; De-Miguel-Luken, Verónica; Jiménez-López, Jesús Salvador (Springer Nature, 2024)
Cesarean sections are the most common abdominal surgical interventions worldwide, with increasing rates in both developed and developing countries. Postpartum (hemorrhage PPH) during cesarean sections can lead to maternal morbidity, prolonged hospital stays, and increased mortality rates. Although various non-surgical measures have been recommended for PPH prevention, surgical techniques such as uterine artery ligation and embolization have been used to manage PPH effectively. Objective This study aimed to evaluate the effectiveness of a surgical technique based on the temporary bilateral clamping of uterine arteries to reduce blood loss during cesarean sections. Methods A longitudinal prospective, randomized, controlled study was conducted with a preliminary population group of 180 patients at the University Hospital Regional de Málaga from November 2023 to January 2024. The study protocol was approved by the Ethics Committee of the Regional University Hospital of Malaga (protocol 1729-N-23 and registred with ISRCTN15307819|| http://www.isrctn.org/, Date submitted 12 June 2023 ISRCTN 15307819). The patients were divided into two groups based on whether the clamping technique was applied during their cesarean sections. The study assessed hemoglobin levels before and after surgery, hospitalization durations, and t he prevalence of anemia at discharge as the primary outcomes. Results The patients who underwent the clamping technique demonstrated significant reductions in hemoglobin differences (0.80 g/dL) compared to the control group (1.42 g/dL). The technique also resulted in shorter hospital stays (3.02 days vs. 3.90 days) and a lower prevalence of anemia at discharge (76.2% vs. 60%). Conclusion Temporary clamping of uterine arteries during cesarean sections appears to be an effective measure for preventing postpartum hemorrhaging, reducing hospital stays, and decreasing the prevalence of anemia at discharge. Further research with larger sample sizes and standardized indications is warranted to confirm the benefits and potential broader applications of this technique. Trial registration ISRCTN 15,307,819
Keywords: Cesárea; Utero - Hemorragia - Prevención; Uterine artery clamping; Surgical maneuvers; Cesarean bleeding; Bleeding prevention